Overcoming Identity Threat: Using Persona Pedagogy in Intersectionality and Inclusion Training - Cate Thomas (Social Sciences, 2022)
There are many efforts and strategies in place to increase the inclusivity of workplaces which is a positive approach, but little thought is provided to the personal cost of participants in undertaking some of these initiatives. Often due to the choice of pedagogy, participants may be placed in the situation to reveal hidden parts of their identity which leads to vulnerability and unpredicted exposure in the workplace and organisation. The paper examines the key issue of identity threat whilst undertaking inclusion and intersectional-type training. The paper highlights the continued need to challenge bias and other forms of exclusionary behavioural and cultural practices, however, this must be carried out in a cautious manner to uphold the safety of well-being of all individuals. A solution to minimize or overcome identity threat is offered via the use of persona pedagogy where personas are used expands one’s own world views and limits vulnerability exposure. The persona approach initiates experiences different to an individual’s lived experience which evokes critical reflection of one’s own positionality by taking on another persona. The paper concludes that the use of persona pedagogy leads to true transformative learning in the workplace whilst protecting the identity of individuals.